2019
DOI: 10.1016/j.aott.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Long term survival analysis of cementless Spotorno femoral stem in young patients

Abstract: ObjectiveThe aim of this study was to analyze the survivorship and clinical outcome of Cementless Spotorno (CLS) stem in young patients.MethodsA total of 99 consecutive hip arthroplasties using CLS stem were performed on 84 patients younger than 50 years of age between 1993 and 2001. 63 patients were available for final follow-up (mean age: 39 ± 7.8 (range: 22–50)). Patients' Harris Hip Scores (HHS) and survivorship estimates were calculated. Radiographs were analyzed for acetabular implant status, canal fill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The results of this study group are comparable to to previous published cohorts as shown by Delauny, giving survival rates of 99% for aseptic loosening after a timespan of 7 to 8 years [1]. Other stems with excellent long term results in younger patients such as CLS Spotorno (72.8 any reason after 23.8 years) [10,12,11], Bicontact (93.57% at 12 years) [6,5] and Corail (95% at 12 years) [8,9] show good results up to 24 years of follow-up, but none of the mentioned cohorts give results for a period up to the end of the third decade as we do. Published data does sometimes not focus on the long-term problems such as wear of early polyethylene liners, therefore the reason for aseptic loosenings stays unclear in most cases.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study group are comparable to to previous published cohorts as shown by Delauny, giving survival rates of 99% for aseptic loosening after a timespan of 7 to 8 years [1]. Other stems with excellent long term results in younger patients such as CLS Spotorno (72.8 any reason after 23.8 years) [10,12,11], Bicontact (93.57% at 12 years) [6,5] and Corail (95% at 12 years) [8,9] show good results up to 24 years of follow-up, but none of the mentioned cohorts give results for a period up to the end of the third decade as we do. Published data does sometimes not focus on the long-term problems such as wear of early polyethylene liners, therefore the reason for aseptic loosenings stays unclear in most cases.…”
Section: Discussionsupporting
confidence: 84%
“…Some studies describe longterm results up to 20 years [4]. Other well established stem systems are reported to have excellent long term results such as Bicontact [5,6], Taperloc [7], Corail [8,9], CLS [10][11][12] as well as threaded cups such as T-TAP ST [13].…”
Section: Introductionmentioning
confidence: 99%
“…Within the Czech arthroplasty register, 2677 evaluated stems showed a survival rate of 99.81% after 1 to 11 years [30]. Other stems with excellent long-term results in younger patients such as CLS Spotorno (72.8 any reason after 23.8 years) [10][11][12], Bicontact (93.57% at 12 years) [5,6], and Corail (95% at 12 years) [8,9] show good results up to 24 years of follow-up, but none of the mentioned cohorts give results for a period up to the end of the third decade as we do. Published data does sometimes not focus on the long-term problems such as wear of early polyethylene liners; therefore, the reason for aseptic loosenings stays unclear in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies describe long-term results up to 20 years [ 4 ]. Other well-established stem systems are reported to have excellent long-term results such as Bicontact [ 5 , 6 ], Taperloc [ 7 ], Corail [ 8 , 9 ], and CLS [ 10 12 ] as well as threaded cups such as T-TAP ST [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 , 6 In a recent study, the cementless Spotorno ® femoral stem, even in young patients, has been reported to have a survival rate of 91.2% after 18 years, when all causes are considered, and the rate reaches 95.1% when infection is excluded. 7 With the femoral stem of the CLS system having such a high survival rate, we wanted to determine the survival rate of the expansive acetabular component and the total prosthesis.…”
Section: Introductionmentioning
confidence: 99%